2021
DOI: 10.5812/compreped.109539
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Neonatal Jaundice Requiring Exchange Transfusion

Abstract: Background: Neonatal jaundice is highly prevalent in Asia and has serious complications, such as kernicterus. Therefore, it is very important to identify the risk factors of jaundice requiring exchange transfusion since it can be helpful in the prevention of the disease and early diagnosis of its complications. Objectives: The present study aimed to identify the causes of neonatal jaundice requiring blood exchange. Methods: The present cross-sectional study was performed on 251 term and preterm neonates. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Extreme hyperbilirubinemia, defined as TSB ≥ 25 mg/dL [18] was noted in 3(1.9%) in this study , unlike a study from Taiwan [4] which had shown that (111) neonates (26.9%) of the sample were with marked hyperbilirubinemia .The Taiwanese study has shown that ABO incompatibility was the reason for neonatal hyperbirubinemia in (21.8%) of the cases .In this study 3(1.9%) of the neonatal jaundice was caused by urinary tract infections, a study from Taiwan had concluded that (0.6%) of the neonates only were diagnosed with urinary tract infection as the cause of jaundice (N=413) [4].An Iranian study had concluded that urinary tract infection causes (5.1%) of neonatal hyperbilirubinemia [6]. Although this study had shown that there was a weak, positive correlation between neonatal weight on admission and total serum bilirubin , the two authors of this study believed that this result could be due to confounding factors as other studies had shown that total serum bilirubin is inversely related to neonatal age [19] other studies had shown that although weight loss did not seemed it was the etiology of hyperbilirubinemia but the possibility that it had aggravated the jaundice is great [20,21].…”
Section: Discussionmentioning
confidence: 85%
“…Extreme hyperbilirubinemia, defined as TSB ≥ 25 mg/dL [18] was noted in 3(1.9%) in this study , unlike a study from Taiwan [4] which had shown that (111) neonates (26.9%) of the sample were with marked hyperbilirubinemia .The Taiwanese study has shown that ABO incompatibility was the reason for neonatal hyperbirubinemia in (21.8%) of the cases .In this study 3(1.9%) of the neonatal jaundice was caused by urinary tract infections, a study from Taiwan had concluded that (0.6%) of the neonates only were diagnosed with urinary tract infection as the cause of jaundice (N=413) [4].An Iranian study had concluded that urinary tract infection causes (5.1%) of neonatal hyperbilirubinemia [6]. Although this study had shown that there was a weak, positive correlation between neonatal weight on admission and total serum bilirubin , the two authors of this study believed that this result could be due to confounding factors as other studies had shown that total serum bilirubin is inversely related to neonatal age [19] other studies had shown that although weight loss did not seemed it was the etiology of hyperbilirubinemia but the possibility that it had aggravated the jaundice is great [20,21].…”
Section: Discussionmentioning
confidence: 85%
“…Modalities like IVIG and anti-D administration have also demonstrated potential in raising the threshold for exchange transfusion. 15,21 The data gleaned from our neonatal unit regarding exchange transfusion underscores not only the strain on available resources but also the demand for well-trained healthcare personnel. It is imperative to devise guidelines and strategies tailored to the unique circumstances of local neonatal units, taking into account the insights garnered from our study.…”
Section: Table-ii Comparison Of Risk Factors For Exchange Transfusion...mentioning
confidence: 99%
“…Os tratamentos terapêuticos para icterícia são a fototerapia, administração de medicamentos e a exsanguinotransfusão (EXT). A recomendação do tratamento vai depender da concentração de bilirrubina no sangue do neonato (Dantas et al, 2018;Boskabadi et al, 2021). Ressaltando-se, pois, que a fototerapia de luz é o tratamento convencional comumente usadomundialmentepara o controle de icterícia, isso ocorre devido, sobretudo, à sua simplicidade de operação e resultados promissores (Pettersson et al, 2021;Freitas et al, 2022).…”
Section: Introductionunclassified